Madrasah Head's Strategy in Improving Teacher Pedagogical Competence at MTSN 1 Bondowoso - Siti Fatimah; Zainul Arifin (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
The madrasa head's strategy is that the decision of the success of an educational institution is very dependent on the availability of quality human resources (HR) among educators and supporting institutions. Educators are said to have pedagogical competence. As in Republic of Indonesia Law No. 14 of 2005, a teacher's pedagogical competence is in recognizing student characteristics to be able to actualize their potential, the ability to plan and evaluate the implementation of learning. The focus of the research is on the principal's leadership strategy which must be constructed based on the teacher's pedagogical circumstances and abilities in assessing the needs, changes and development of the learning environment with aspects of togetherness and diversity of students so that there is a need for new methods that focus more on experience in the field as carried out by the principal. Madrasah Tsanawiyah Negeri 01 Bondowoso school. The research method used in this research uses data collection methods used through interviews, observation, interviews, and documentation. The data analysis technique used in this research is the Miles Hubberman data analysis technical model, namely data collection, data reduction, data display, and data verification. In this research, triangulation techniques are used as a technique for data validity.